Comparison of Early Measurements of the Distraction Index, Norberg Angle on Distracted View and the Official Radiographic Evaluation of the Hips of 215 Dogs from Two Guide Dog Training Schools - Taroni, Mathieu; Genevois, Jean-Pierre; Viguier, Eric; Pillard, Paul; Livet, Véronique; Cachon, Thibaut; Carozzo, Claude (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives The main purpose of this article is to evaluate the correlation between the distraction index (DI) and Norberg angle values in distracted hips (distraction Norberg angle, DNA) at 4 months of age and the official hip score based on the Fédération Cynologique Internationale (FCI) grid at 12 months of age.Methods For dogs (n = 215) from two guide dog training organizations, the DI and DNA were measured by a single expert on distraction radiographs performed at 4 months of age. The FCI score was determined by the same expert at 12 months of age on a standard hip-extended view.Statistical analysis included receiver operating characteristic curve analysis and concordance correlation coefficient calculation.Results The mean DI was 0.48, the mean DNA was 86.5° and 59.5% of hips had an A FCI score. The concordance correlation coefficient of DI and DNA was 0.78. The DI threshold for D- and E-scored hips that was associated with the least misclassification was 0.58 (sensitivity [Se] = 0.6, specificity [Sp] = 0.82). The DNA threshold that was associated with the least misclassification was 85° (Se = 0.83, Sp = 0.68).Clinical Significance DNA has a fair correlation with DI at 4 months and reflects hip passive laxity. D and E FCI scores at 12 months cannot be reliably predicted from the 4 months value of DI or DNA but 96% of hips with DI < 0.58 at 4 months had an A, B or C FCI score at 12 months of age. Similarly, 98% of hips with DNA > 85° at 4 months had an A, B or C FCI score at 12 months of age.
Keywords: hip dysplasia; distraction index; distracted Norberg angle; FCI grade